P1-S2.37 Incidence of urethral discharge syndrome among men who have sex with men and associated risk factors in India; a cohort analysis of clinic attendees. (10th July 2011) - Gurung, A; Das, A; Naryanan, Prakash; Neilson, G; Morineau, Guy; George, Bitra
Abstract : Background: Monitoring data from a cohort of men who have sex with men (MSM) attending 421 clinics located in six states of India from January 2004 to December 2009 were studied. These clinics were supported by Avahan (the India AIDS initiative of the Bill & Melinda Gates Foundation) and provided services for sexually transmitted infections (STIs) including presumptive treatment for gonorrhoea and chlamydia; risk reduction counselling, treatment of STI syndromes and regular STI check-ups. Methods: Individual tracking data from the clinical forms were collected, merged and cleaned. Observed episodes of urethral discharge (UD) were counted as incident cases when clinical record prior to the episode reported no UD or if the patients had received the clinics' standard single dose directly observed treatment. The mid-point between visits was considered as the time of incident UD. Cox proportional hazard models were used to assess associations between incidence of UD and reported behaviours. Results: A total of 82 690 MSM made 508 469 visits to the clinics, constituting a cohort of 88 458 person-years (median duration of follow-up 0.86 years; maximum, 5.9 years). 7292 cases of UD were considered as incident giving an incidence rate (IR) of 8.2 per 100 person years (PYs). The IR decreased from 82.7 per 100 PYs in 2005 to 2.8 per 100 PYs in 2009; the first year of follow-up having the highest incidence (HR =1.5, p<0.001). Factors influencing the risk of UD were—number of years in commercial sex; the first year being the most risky, (HR=4.3, p<0.001); having more than ten clients per week (HR=1.6, p<0.001); not using condoms at last sex (HR=2.3, p<0.001); self-reported sexual identity of a penetrative role in anal sex (HR=1.4, p<0.001), and not receiving treatment in the first three clinic visits, (HR=2.8, p<0.001). Increasing frequency of clinic visits per year had a protective role (HR=0.9, p<0.001). MSM visiting the clinics more than five times a year had an IR below 1 per 100 PY. While one-time presumptive treatment increased the risk of UD (HR=3.2, p<0.001), there were no episodes of UD when the treatment was given at more than one consecutive visit. Conclusion: Urethral discharge syndrome among MSM shows a decline and could be a good proxy to include in future STI surveillance in resource-constrained scenarios. An analysis of MSM risk behaviour in India can help in risk profiling for targeted interventions.